Improvement Rangka Sepeda Motor Listrik Dengan Daya 10 Kw Akibat Deformasi - Achmad Suhendar (2023)
The problem of environmental pollution from the use of motorized vehicles is one of the things that must be considered because it contributes the most air pollution. From the problems above, a solution must be found to solve this problem by changing conventional vehicles to electric vehicles. In this study, the frame design of an electric motorcycle with a power of 10 kW was carried out. The materials used are AISI 1015 and Aluminum 6061. The load that occurs in the frame design is the mass of two passengers assuming a load of 70 kg each. The mass of the propulsion system is 50 kg with static testing. The simulation results using AISI 1015 material with a thickness of 3 mm produced a maximum stress of 62.37 MPa and a displacement of 0.4564 mm and a safety factor of 4.57. The simulation results using Aluminum 6061 material with a thickness of 3 mm produced a maximum stress of 61.22 MPa and a displacement of 1.36 mm and a safety factor of 4.49. The framework that has been completed with the analysis process still shows opportunities for optimization and it is still very possible to reduce the value of the safety factor which is still quite high by changing the thickness of the material used. The results of the frame optimization simulation resulted in a maximum stress of 101.2 MPa and a displacement of 2.645 and a safety factor of 2.72. The most optimal material for the frame of an electric motorbike with a power of 10kW in this study is 6061 aluminum with a thickness of 2 mm.